Physiology and pathophysiology of female sexual function - Hilz, Max-Josef; Wang, Ruihao (Elsevier, 2022)
Female sexual dysfunction (FSD) affects many million women. The FSD prevalence can be as high as 43% among women younger than 60 years. Classifications include disorders of desire, arousal, orgasm, and pain. Revised DSM-5 definitions include female sexual interest/arousal disorder (FSIAD), genitopelvic pain/penetration disorder (GPPD), and female orgasmic disorder (FOD). Sexual function requires interaction of multiple levels and areas of the central and peripheral somatic and autonomic nervous system. Among central areas involved in arousal and sexual responses are the ventral medullary reticular formation, nucleus paragigantocellularis in the ventral medulla, periaqueductal gray, mesencephalic ventral tegmental area, neurons in the central tegmental mesencephalic region, the medial amygdala, and the medial preoptic area (MPOA). Central neurotransmitters include dopamine (enhances sexual desire, arousal), norepinephrine (gates sensory input from genitalia and maintains sexual arousal), acetylcholine (mediates lubrication and vaginal engorgement), histamine, serotonin (diminishes excitatory effects, interferes with arousal and orgasm), prolactin (causes sexual satiety and postorgasmic relief), oxytocin (promotes sexual receptivity and bonding). Peripheral sympathetic and parasympathetic pathways are similar in men and women. Hormones influence female sexual function. Progesterone furthers partner-receptivity, estrogens enhance desire, arousal, sensory thresholds, and genital arterial blood flow. Testosterone helps initiate sexual activity. FSD etiologies include psychogenic and psychiatric disorders; cardiovascular, neurological, muscular, endocrine problems; infectious diseases; or medications such as selective serotonin reuptake inhibitors (SSRIs), and many others. Therapeutic approaches of FSD mainly include psychoeducation, estrogen replacement, pain treatment physiotherapy, or biofeedback.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biofeedback; Estrogen replacement; Female sexual dysfunction; Female sexual function; Pain treatment physiotherapy; Psychoeducation